2013
DOI: 10.1177/1420326x13508145
|View full text |Cite
|
Sign up to set email alerts
|

Domestic laundering: Environmental audit in Glasgow with emphasis on passive indoor drying and air quality

Abstract: As the UK and Scottish governments aim for zero-carbon housing, with tightly sealed building envelopes becoming paramount, indoor air quality (IAQ) and its implications for health has become a concern. This context relates to the reported findings of a 2008-2011 study, 'Environmental Assessment of Domestic Laundering', concerning the prevalence of passive indoor drying (PID). Assessment of PID impacts, shaped by built and social context including occupants' habits and trends, draws on monitored data from 22 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…However, poor ventilation rates are seen in bedrooms with more frequent window opening – which compromises the air-tightness – and previous research has identified similar conditions in dwellings that are not particularly airtight. 74 The focus then shifts towards the nature of the ventilation strategies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, poor ventilation rates are seen in bedrooms with more frequent window opening – which compromises the air-tightness – and previous research has identified similar conditions in dwellings that are not particularly airtight. 74 The focus then shifts towards the nature of the ventilation strategies.…”
Section: Discussionmentioning
confidence: 99%
“…In OC1 for example estimated ventilation rates, with single occupancy were 4.58 l/s/p – the measured MVHR supply rate for this room was 6.98 l/s. The disabling of the system will reduce ventilation rates with consequent effects on CO 2 levels 74 and there are several instances noted where this has occurred, the most common explanation being that this is conceived of as a heating system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations